2018
DOI: 10.1017/s1357321717000241
|View full text |Cite
|
Sign up to set email alerts
|

A review of Solvency II: Has it met its objectives?

Abstract: Solvency II is currently one of the most sophisticated insurance regulatory regimes in the world. It is built around the principles of market consistency and embedding strong risk management and governance within insurance companies. For business with long-term guarantees, the original basis produced outcomes that were unacceptable to the member states. The original design was amended through Omnibus II. The working party has looked back at the outcome of the final regulation and comments on how well Solvency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 5 publications
0
14
0
3
Order By: Relevance
“…d 3 μ is the part of the fund that moves out of the risk state. Condition (5) requires that the difference between this part and the part that flows in the risk state should not be less than the fluctuation range. In fact, the fund that moves out of the risk state should be able to resist the risk faced by the fund that is in the risk state; that is to say, the insurance organization should make appropriate adjustment and control according to the investment status in order to ensure the system to enter a stable state.…”
Section: Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…d 3 μ is the part of the fund that moves out of the risk state. Condition (5) requires that the difference between this part and the part that flows in the risk state should not be less than the fluctuation range. In fact, the fund that moves out of the risk state should be able to resist the risk faced by the fund that is in the risk state; that is to say, the insurance organization should make appropriate adjustment and control according to the investment status in order to ensure the system to enter a stable state.…”
Section: Results Analysismentioning
confidence: 99%
“…Cooke et al [4] also found that Solvency II reduces the impact of risk margin and reduces the technical reserve of insurance companies. Rae et al [5] believed that Solvency II has not achieved the expected goal, and there are still some areas that need to be adjusted and improved in terms of procyclicality and market consistency. Pablo Duran etal.…”
Section: Analysis Of Solvency Supervision Systemmentioning
confidence: 99%
“…In addition to harmonizing the EU insurance market and improving EU insurers’ competitiveness, Solvency II mainly aims at promoting a more resilient regulation, effective risk management and transparency (see, for instance, Rae et al. 2018 and Hopt 2013 ).…”
Section: Some Regulatory Issuesmentioning
confidence: 99%
“…For instance, the United Kingdom was early in introducing capital requirements that were sensitive to duration matching (Swain & Swallow, 2015) and Solvency II has been evolutionary, rather than revolutionary. For Germany, where the regulatory regime has been based around historical cost accounting, Solvency II has been a large change (Rae et al., 2018). This suggests that, particularly in Germany, regulatory constraints varied over time.…”
Section: Why Do Life Insurers Bear Interest Rate Risk?mentioning
confidence: 99%